Pendidikan Pembebasan : Telaah Terhadap Pemikiran Paulo Freire - Idris, Muh. (IAIN Samarinda, 2009)
Nowadays, education tends to ignore the value of human being which consists of the liberation. The liberation value in human individual is taken by another person who yells out democracy. We can find the real fact in reality where one person takes another personâ€™s right through an institution with democracy and quality reasons. An education scientist, Paulo Freire, gives an illustration that education today through formal institution makes robot in human who work as mechanic machine, where their independent to act and express the ideas is limited. In simple way, Freire points out that, â€œThe absolute consistency will make life becomes worthless, discolor, and cannot be felt experience.â€ Based on the statement above, Freire has deschooling concept, the concept of study without schooling. Itâ€™s because the study can be done out of the formal school even in outdoor condition.